2007
DOI: 10.1002/polb.21334
|View full text |Cite
|
Sign up to set email alerts
|

Field‐theoretic simulations of polyelectrolyte complexation

Abstract: This viewpoint article is intended as a brief introduction to the emerging subject of field-theoretic simulations (FTS) of charged polymers. While the direct numerical simulation of field theory models has begun to impact several traditional areas of polymer science, including blends and block copolymers, polyelectrolytes have hitherto not been the subject of field-theoretic simulations.Here we report on a preliminary FTS study of polyelectrolyte complexation that demonstrates the potential of this novel numer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 51 publications
2
97
0
Order By: Relevance
“…The model considered in this work is similar to that considered in previous field-theoretic studies of polyelectrolyte systems exhibiting complex coacervation 22,23 with some modifications. For completeness and to highlight some of the differences between our field-theoretic model and previous incarnations of the model, we will recount the model in detail.…”
Section: A Polyelectrolyte Modelmentioning
confidence: 65%
See 2 more Smart Citations
“…The model considered in this work is similar to that considered in previous field-theoretic studies of polyelectrolyte systems exhibiting complex coacervation 22,23 with some modifications. For completeness and to highlight some of the differences between our field-theoretic model and previous incarnations of the model, we will recount the model in detail.…”
Section: A Polyelectrolyte Modelmentioning
confidence: 65%
“…One challenge of adopting the field-theoretic approach is that it is a relatively new class of simulation, and therefore the techniques to calculate important material properties (e.g., the interfacial tension ) have not yet been developed. In this study, we extend the previous FTS of complex coacervation 22,23 by characterizing the interfacial properties between the coacervate and the solvent. Density profiles are calculated, and we adapt two techniques from the literature on particle-based simulations to calculate the interfacial tension from fieldtheoretic simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used Complex-Langevin simulations to look at fluctuation effects in pure symmetric diblocks. Since then, Fredrickson and coworkers have shown that the method can be extended in various ways, e.g., it can deal with external stresses [225]), and it can be applied very naturally to charged polymers [226,227]. Nevertheless, there are still problems with it.…”
Section: Field-based Modelsmentioning
confidence: 99%
“…It is also useful to point out that polyelectrolyte condensation theory remains incomplete and that charged polymers are some of the most difficult systems to study theoretically or by simulations. [16] To address this problem, we examine herein the interactions between poly1 20 and ssDNA by a combination of photoluminescence (PL) spectroscopy, FRET studies and liquid phase AFM. Correlation of optical properties in water with size distributions on a surface provides insight into the correct physical features and structural dynamics of these nanoscalar polyelectrolyte complexes.…”
Section: Introductionmentioning
confidence: 99%